Experimental investigation of pool boiling heat transfer on the radial micro-pillar surfaces. (September 2022) - Zhang, Yonghai; Ma, Xiang; Zhou, Jie; Lei, Zeyang; Wei, Jinjia
Highlights: The radial micro-pillar surfaces can enhance CHF and HTC by up to 200% and 275%, respectively. The distribution of radial micro-pillars can effectively control ONB. The heat transfer area enhancement ratio has a significant effect on the CHF especially at a high subcooled temperature. The maximum HTC enhancement ratio is also constant when ΔTsub  > 15 K. Abstract: An experimental study on the pool boiling heat transfer with heterogeneous micro-pillar surfaces was performed in this study. Six kinds of surfaces, including single-block radial micro-pillar surfaces (MS-1, MS-2 and MS-3) and four-blocks radial micro-pillar surfaces (BS-1, BS-2 and BS-3), were fabricated by the dry etching technique. FC-72 was used as the working medium under four different liquid subcoolings. A high-resolution camera was used to capture the boiling phenomenon. It could be found that the heat transfer performance of these radial micro-pillar surfaces was remarkably enhanced in comparison with that of a smooth surface, which showed an earlier onset of nucleate boiling (ONB) and an improved heat transfer coefficient (HTC). Moreover, the critical heat flux (CHF) was dependent on the heat transfer area enhancement ratio at the high subcooled temperature. BS-1 surface had the highest CHF 1.57–2.05 times more than the smooth surface. For the MS-1 and BS-2 surfaces, their CHF was almost the same due to a similar heat transfer area enhancement ratio, but the HTC of the MS-1 increased by 20% compared with the BS-2 surface. This could be due to different solid fractions φS (36.78% for MS-1 and 25.81% for BS-2). Under the saturation condition, the overall HTC of micro-pillar surfaces first increased to a critical value, and then decreases with the increase of heat flux. In addition, the maximum heat transfer coefficient enhancement ratio (HTC max, PF /HTC max, S ) was almost constant when ΔTsub  > 15 K, which was somewhat significant for subcooled pool boiling.